MEDIA AUDIO VISUAL TERKAIT PERILAKU KESADARAN HIDUP BERSIH DAN SEHAT BAGI ANAK USIA DINI : Studi Analisis Konten Video Animasi Perilaku Hidup Bersih dan Sehat - Desti Amalia, - (2020)
This research was motivated by audio-visual learning media on the YouTube site related to the animated video on Clean and Healthy Living Behaviors for early childhood, which consists of animated videos of washing hands, brushing teeth, taking out trash and healthy and nutritious food that is not in accordance with the concept or material of Life Behavior. Clean and healthy. The purpose of this study was to determine the material contained in the animated video on a clean and healthy lifestyle, and to find out the delivery of an animated video about a clean and healthy lifestyle in accordance with the concept of a clean and healthy lifestyle. This study used a content analysis method with a qualitative approach with the object of research on animated videos on the flatfaoam YouTube site about healthy and healthy living behaviors. Data collection techniques using video documentation study Periaku live clean and healthy. The data analysis technique uses a content analysis scheme. The results showed that the video animation related to clean and healthy living habits, the material presented in the video did not contain the delivery of material on clean and healthy living behavior in accordance with the concept or material of clean and healthy living behavior. Thus, video content containing learning material for clean and healthy living habits should contain material that is in accordance with the concept or material for clean and healthy living habits, so that the learning video can be an audio-visual learning medium for early childhood.